Efektivitas Pupuk Organik Cair Daun Lamtoro dan Biocar Sekam Padi terhadap Pertumbuhan Tanaman Kailan (Brassica Oleraceae L.) - Purba, Febriyandi; Panggabean, Ellen L. (Jurnal Ilmiah Pertanian ( JIPERTA), 2026)
This study was conducted to evaluate the effect of liquid organic fertilizer (LOF) from lamtoro leaves and rice husk biochar on the growth of kale (Brassica oleraceae). The research was motivated by the low productivity of kale in Indonesia due to the lack of sustainable cultivation practices, thus requiring environmentally friendly fertilization alternatives. The experiment was carried out at the experimental field of the Faculty of Agriculture, Universitas Medan Area, from August to September 2024, using a factorial randomized block design (RBD). The rice husk biochar factor consisted of 4 levels: P0 (without biochar), P1 (1.44 kg/plot), P2 (2.88 kg/plot), and P3 (4.32 kg/plot). The lamtoro leaf LOF factor also consisted of 4 levels: N0 (without LOF), N1 (100 ml/900 ml water), N2 (200 ml/800 ml water), and N3 (300 ml/700 ml water). Thus, 16 treatment combinations were obtained. Observed parameters included plant height, number of leaves, fresh weight per sample, fresh weight per plot, economic yield, and root weight. The results showed that rice husk biochar significantly affected plant height, number of leaves, fresh weight per sample, fresh weight per plot, and economic yield per sample plant, with the best treatment at a dose of 4.32 kg/plot (P3). Meanwhile, lamtoro leaf LOF significantly affected economic yield per plot, with the best treatment being N3 (300 ml/700 ml water). The combination of both treatments had no significant effect on all observed parameters.